Urban Planet Knowledge towards Sustainable Cities - Elmqvist, Thomas; Bai, Xuemei; Frantzeskaki, Niki; Griffith, Corrie; Maddox, David; McPhearson, Timon; Parnell, Susan; Romero-Lankao, Patricia; Simon, David; Watkins, Mark (Life Sciences, 2018)
Global urbanization promises better services and stronger economies but also carries risks and unforeseeable consequences. Urban Planet highlights the hopes and hindrances of our journey of urbanization and the need for a parallel evolution of our science and systems to ensure we reap the rewards. This title is also available as Open Access.